Medicines Used in Heart Failure (Global Scientific Review, 2022)
Dear reader, this article provides information about the drugs used in heart failure, one of the diseases that are currently common ingangj . For most people, Heart Failure is a long-term condition that cannot be treated. But treatment can help keep symptoms under control, possibly for many years. The main treatment options are: healthy lifestyle changes, medications, devices installed on your chest to control heart rhythm, surgery. In most cases, a combination of treatment is required.